Morphology of the ablated gall-bladder from the short-scar incision in patients with acute cholecystitis - A. V. Kapshitar (Patologìâ)
Aim. Acute cholecystitis is the most frequent pathology among the acute surgical diseases of abdominal cavity organs. The aim of the research was the investigation of morphological forms of acute cholecystitis and their comparison with histologycal conclusion.